1987
DOI: 10.1007/bf00390037
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic ratio of mono or combination bacterial lipopolysaccharide therapy in methylnitrosourea ? induced rat mammary carcinoma

Abstract: Four experiments investigating the antitumor activity of bacterial lipopolysaccharide (LPS) against the autochthonous methylnitrosourea-induced mammary carcinoma are summarized. Administration of LPS alone i.v. caused distinct regression of small tumors following its first injection. This therapeutic effect, however, was short-lived and could not be maintained by administering a second dose. The observed antineoplastic activity of LPS was dose-related, whereas no dose-response relationship was observed with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This study on the role of IL-2 in established autochthonous mammary and colorectal cancers was intended to investigate its efficacy in models more relevant to the human situation [10,12,19]. Both models have been characterized by a number of chemotherapeutic studies and have been considered useful for the preclinical evaluation of new cytostatic agents [3][4][5]27] as well as biological response modifier [6,19]. Differences between the clinical and the experimental situation described, however, should be noted: patients usually undergo surgical intervention, and subsequent therapy is given to treat metastatic disease, whereas the IL-2 treatment in this study was given to treat primary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…This study on the role of IL-2 in established autochthonous mammary and colorectal cancers was intended to investigate its efficacy in models more relevant to the human situation [10,12,19]. Both models have been characterized by a number of chemotherapeutic studies and have been considered useful for the preclinical evaluation of new cytostatic agents [3][4][5]27] as well as biological response modifier [6,19]. Differences between the clinical and the experimental situation described, however, should be noted: patients usually undergo surgical intervention, and subsequent therapy is given to treat metastatic disease, whereas the IL-2 treatment in this study was given to treat primary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported, however, that they were unable to produce sufficient anticancer therapy with acceptable toxicity using this approach. 49 …”
Section: Relevance Of Tolerance To the Use Of Lps/lipid A In Cancermentioning
confidence: 99%